2016
DOI: 10.1007/s13311-015-0405-3
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimmunotherapies Targeting T Cells: From Pathophysiology to Therapeutic Applications

Abstract: Therapeutic options for multiple sclerosis (MS) have significantly increased over the last few years. T lymphocytes are considered to play a central role in initiating and perpetuating the pathological immune response. Currently approved therapies for MS target T lymphocytes, either in an unspecific manner or directly by interference with specific Tcell pathways. While the concept of BT-cell-specific therapyî mplies specificity and selectivity, currently approved approaches come from a general shaping of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 163 publications
(144 reference statements)
0
29
0
Order By: Relevance
“…Efforts have focused on the understanding MS pathogenesis and the development of effective MS therapeutics. Substantial progress has been made in MS research, and therapeutic options have increased in recent years67. However, the exact molecular mechanisms underlying the onset and progression of MS remain largely unknown and a salient challenge.…”
mentioning
confidence: 99%
“…Efforts have focused on the understanding MS pathogenesis and the development of effective MS therapeutics. Substantial progress has been made in MS research, and therapeutic options have increased in recent years67. However, the exact molecular mechanisms underlying the onset and progression of MS remain largely unknown and a salient challenge.…”
mentioning
confidence: 99%
“…Consequently, an alternative treatment approach in MS could aim to selectively restore self-tolerance to auto-antigens via immunization [160] and epitope-specific induction of T cell tolerization [161] or specifically by targeting regulatory T cells (Treg) signaling [162]. Antigen-specific therapies in MS have been reviewed [163,164]. A first phase I trial in humans published in 2013 showed that the antigen-coupled cell tolerization in MS is feasible and safe [165].…”
Section: T-cell Directed Strategiesmentioning
confidence: 99%
“…natalizumab, fingolimod) or indirectly via broad effects on the immune system (e.g. glatiramer acetate, interferon beta) [7,8]. Moreover, T cell depletion approaches were also evaluated, unfortunately without success.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, T cell depletion approaches were also evaluated, unfortunately without success. Anti-CD3-(Muromonab) and anti-CD4-directed therapies (Priliximab) failed to show efficacy in humans, had limited therapeutic potential and/or exerted serious adverse effects [7]. Since interferon beta (IFN-β) preserves its long-term safety and efficacy, it is widely used as first-line treatment for MS. Meta-analysis of clinical trials indicates that IFN-β reduces MS relapses and attenuates novel inflammatory lesions, although many patients do not respond to the treatment [9].…”
Section: Introductionmentioning
confidence: 99%